An Update for Pharmacologists on New Treatment Options for Inflammatory Bowel Disease: The Clinicians’ Perspective - Schmidt, Carsten; Grunert, Philip C.; Stallmach, Andreas (Frontiers in Pharmacology, 2021)
The introduction of anti-tumor necrosis factor antibodies resulted in a considerable expansion of the options available for the treatment of inflammatory bowel disease. Unfortunately, approximately one third of treated patients do not respond to these modalities, and drug efficacy may be lost over time. These drugs are also associated with contraindications, adverse events, and intolerance. As such, there is an ongoing need for new therapeutic strategies. Despite several recent advances, including antibodies against pro-inflammatory cytokines and cell adhesion molecules, Janus kinase inhibitors, and modulators of sphingosine-1-phosphate receptors, not all problems associated with IBD have been solved. In this manuscript, we review the current state of development of several new treatment options. Ongoing evaluation will require specific proof of efficacy as well as direct comparisons with established treatments. Results from head-to-head comparisons are needed to provide clinicians with critical information on how to formulate effective therapeutic approaches for each patient.